Research on optimization of a high precision hydrostatic turntable - Hu, Lai; Chen, Yaolong (Manufacturing Technology Journal, 2020)
This paper mainly studies the hydrostatic turntable of precision milling and grinding compound machining center in aerospace processing equipment, and innovatively designs and analyzes the mesa. It is proposed to replace the traditional 40Cr with imported marble for the mesa. Firstly, the vibration model of the hydrostatic turntable is carried out. ANSYS Workbench software is used to compare and analyze the original and marble materials. In the process, the static characteristics and the difference of first-order modes of the two materials are compared. In addition, the analytical results are used for manufacturing. The results show when the applied force reaches the limitation 29400N, the maximum displacement of 40Cr increases sharply to 8.9406μm; while the marble material reaches 2.6μm. Meanwhile, it is obtained that the power consumed by marble is reduced by 39.12% compared with 40Cr. The weight of marble is reduced by 39.36% compared with 40Cr. Marble is about 21.59% higher than 40Cr in the comparison of vibration mode results
Keywords: Milling and grinding compound machining center; Hydrostatic turntable; Innovative design; Compared; Marble